Policies and Implementation of Village Fund Direct Cash Assistance (BLT-DD) during the Covid-19 Pandemic in Central Java: Juridical and Maqasid ash-Shari'a Perspectives - Munajat, Makhrus (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2021)
Abstract: The policy and implementation of Village Fund Direct Cash Assistance (BLT) in Central Java has caused its own problems. On the one hand, he has helped rural communities affected by the Covid-19 pandemic in maintaining their lives and freeing them from food insecurity. On the other hand, the policy and implementation of the Village Fund BLT also drew a lot of protests from the village community, because the distribution was considered unfair. In addition, the policy has also disrupted activities that have broad benefits for the village community. On this basis, this article examines the policy and implementation of Village Fund Direct Cash Assistance (BLT) in Central Java from a juridical and maqasid ash-syari'ah perspective. This study uses a descriptive-analytic method with a juridical and maqāṣid ash-sharī'a approach. Several conclusions have been obtained from the study that has been carried out: first, the Village Fund Direct Cash Assistance (BLT) is a preventive government policy. Second, the Village Fund BLT implementation in Central Java has gone quite well, although some problems accompany it, both related to data collection on prospective beneficiaries and their distribution. Third, from a juridical perspective, the policy signifies that the Indonesian government has implemented justice as well as the mandate of Pancasila and the Constitution of 1945. Meanwhile, according to the perspective of maqāṣīd ash-sharī'a, the policy and implementation of the Village Fund BLT in Central Java have been in line with the objectives of Islamic law (maqāṣīd ash-hyarī'a), both at the primary, secondary, and tertiary levels. The Village Fund BLT has protected the religion, soul, lineage, mind, and property of the poor and vulnerable in Central Java due to the Covid-19 pandemic.Abstrak: Kebijakan dan implementasi Bantuan Langsung Tunai (BLT) Dana Desa di Jawa Tengah telah menimbulkan persoalan tersendiri. Pada satu sisi, ia telah membantu masyarakat desa yang terdampak pandemi Covid-19 dalam mempertahankan hidup dan membebaskan mereka dari kerawanan pangan. Di sisi lain, kebijakan dan implementasi BLT Dana Desa juga menuai banyak protes dari masyarakat desa, karena distribusinya dianggap tidak adil. Selain itu, kebijakan tersebut juga telah menyebabkan kegiatan-kegiatan yang bernilai manfaat luas bagi masyarakat desa menjadi terganggu. Atas dasar hal tersebut, artikel ini mengkaji kebijakan dan implementasi Bantuan Langsung Tunai (BLT) Dana Desa di Jawa Tengah dari perspektif yuridis dan maqasid asy-syari’ah. Penelitian ini menggunakan metode deskriptif analitik dengan pendekatan yuridis dan maqashid syari’ah. Dari kajian yang telah dilakukan diperoleh beberapa kesimpulan: pertama, Bantuan Langsung Tunai (BLT) Dana Desa merupakan kebijakan pemerintah yang bersifat prefentif. Kedua, implementasi BLT Dana Desa di Jawa Tengah sudah berjalan baik, meskipun masalah yang menyertainya, baik terkait pendataan calon penerima bantuan maupun distribusinya. Ketiga, dari perspektif yuridis, kebijakan tersebut juga bermakna bahwa pemerintah Indonesia telah menegakkan keadilan dan sekaligus telah melaksanakan amanah Pancasila dan UUD 1945. Sementara dari perspektif maqasid asy-syari’ah, kebijakan dan implementasi BLT Dana Desa di Jawa Tengah telah selaras dengan tujuan disyariatkannya hukum Islam (maqāṣīd asy-syarī’ah), baik pada tataran primer, sekunder, maupun tersier. BLT Dana Desa telah mampu melindungi agama, jiwa, keturunan, akal pikiran, dan harta benda masyarakat miskin dan rentan yang ada di Jawa Tengah akbat pandemi Covid-19.